Management of Intolerance to Casting the Upper Extremities in Claustrophobic Patients - Issei Nagura; Takako Kanatani; Masatoshi Sumi; Atsuyuki Inui; Yutaka Mifune; Takeshi Kokubu; Masahiro Kurosaka (The Scientific World Journal)
Introduction. Some patients showed unusual responses to the immobilization without any objective findings with casts in upper extremities. We hypothesized their that intolerance with excessive anxiety to casts is due to claustrophobia triggered by cast immobilization. The aim of this study is to analyze the relevance of cast immobilization to the feeling of claustrophobia and discover how to handle them. Methods. There were nine patients who showed the caustrophobic symptoms with their casts. They were assesed whether they were aware of their claustrophobis themselves. Further we investigated the alternative immobilization to casts. Results. Seven out of nine cases that were aware of their claustrophobic tendencies either were given removable splints initially or had the casts converted to removable splints when they exhibited symptoms. The two patients who were unaware of their latent claustrophobic tendencies were identified when they showed similar claustrophobic symptoms to the previous patients soon after short arm cast application. We replaced the casts with removable splints. This resolved the issue in all cases. Conclusions. We should be aware of the claustrophobia if patients showed unusual responses to the immobilization without any objective findings with casts in upper extremities, where removal splint is practical alternative to cast to continue the treatment successfully.